Let's Play Content as a Fiduciary Collateral under Indonesian Law: Potential Challenges - Muhammad Anas Fadli; Muhammad Pravest Hamidi; Farhan Azzahra Edwin; Rayyan Gustio Kevin Aritonang (Universitas Airlangga, 2023)
This paper examines the potential implementation challenges of GR 24/2022, specifically related to Let's Play content as a fiduciary collateral. With the rising popularity amongst the younger generation, Let's Play Content has two issues, namely (i) copyright infringement and (ii) inadequate legal instruments. Utilizing a normative juridical analysis, we found that Let's Play content creators may potentially violate copyright laws if they fail to obtain permission or comply with fair use or fair dealing provisions. Furthermore, the current legal instruments available in Indonesia are found to be insufficient, which creates difficulties for stakeholders to mitigate legal risks. To ensure legal certainty and accurate valuations, the government should add supplementing provisions in the implementing regulations, coordinate with relevant parties and conduct education and training programs for appraisers. These steps are necessary in creating a fair business environment and supporting Indonesia's creative industry growth.